2022
DOI: 10.1186/s12912-022-00806-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of medical material management system app on nursing workload and stress

Abstract: Aims To develop a clinical medical material management App for nurses, in order to reduce their workload and improve the efficacy of medical material management. Design The single-group pre- and post-test experimental design was adopted. Methods The subjects were nurses in the intensive care units of a regional hospital in Hsinchu City enrolled by purposive sampling. Single-group pre-tests and post-tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
0
0
1
Order By: Relevance
“…Evidencia-se que os trabalhadores percebem a informatização como um fator que intensifica o trabalho. No entanto, pesquisa recente revelou que o uso de produtos de tecnologia da informação pode influenciar significativamente no gerenciamento de materiais utilizados no cotidiano da assistência de enfermagem, tendo implicações benéficas na prática clínica, na redução da carga de trabalho, no estresse laboral, no nível de preocupação e na melhora da satisfação dos enfermeiros 25 .…”
Section: /16unclassified
“…Evidencia-se que os trabalhadores percebem a informatização como um fator que intensifica o trabalho. No entanto, pesquisa recente revelou que o uso de produtos de tecnologia da informação pode influenciar significativamente no gerenciamento de materiais utilizados no cotidiano da assistência de enfermagem, tendo implicações benéficas na prática clínica, na redução da carga de trabalho, no estresse laboral, no nível de preocupação e na melhora da satisfação dos enfermeiros 25 .…”
Section: /16unclassified
“…It is evident that workers perceive computerization as a factor that intensifies work. However, recent research has revealed that the use of information technology products can significantly influence the management of materials used in daily nursing care, having beneficial implications in clinical practice, reducing workload, work stress, level of concern and improving nurses' satisfaction 25 .…”
Section: /16mentioning
confidence: 99%